CYBERLITERATURE IN CHINA: LITERATURE AS INDUSTRY - Wati, Wati; Gunawan, Hin Goan (Bambuti, 2020)
The digital revolution has influenced the development of various industrial fields in China, as well as in literature. Various types of literary works were born in the digital space and later developed into a genre called WÇŽngluÃ² wÃ©nxuÃ© ç½‘ç»œ æ–‡å¦ or popularly known as "Cybersastra". This article is an overview of in-depth research on the Cybersastra movement in China, starting from its triggering factors, its pioneers, to its business model from time to time. The Cybersastra movement in China has had a major influence on the literary climate which previously seemed so idealistic, then transformed into competitive digital products based on the basis of supply and demand. Despite the distortion that Cybersastra has caused to the authenticity of Chinese literature, the rapidly developing Cybersastra has succeeded in globalizing Chinese literature. Cybersastra also made the literary climate in China a pop culture industry, which forms the basis of various derivative art industries.